Schwannoma in the Buccal Mucosa-An Unusual Presentation - Jayaprasad Anekar; Krishna S Kumar; Jayalakshmi Baipadavu; H Supriya; Ivin E John (Wolters Kluwer Medknow Publications, 2022)
Intraoral schwannomas are rare benign neural neoplasm that originates from the Schwann cells of the peripheral nerves and present as asymptomatic, solitary, slow-growing, submucosal mass and their occurrence is seen in the second-third decade of life. The most favored intraoral sites are the tongue, palate, buccal mucosa, floor of the mouth, gingiva, and lips. Histopathological examination with immunohistochemistry is the gold standard for the diagnosis. As malignant transformation and recurrence rate is rare, surgical excision is the preferred treatment. This article provides an insight into a rare case of schwannoma of the buccal mucosa with a review of the literature.